Rancang Bangun Game Digital Pembelajaran Bilangan Bulat Berbasis Role Playing Games di SD Islam Al-Huda 2 Kediri - Sarbini, Riska Nurtantyo; Afiyah, Dyah Nurul; Mukminna, Halimahtus (Lembaga Yasin AlSys, 2025)
Currently, it is undeniable that the use of smartphones has penetrated all circles, including young children. In the use of smart phones, in addition to being used for communication media, they are also used as digital game game media. In the study, the researcher combined the learning process with video game games in the learning process of mathematical integer operations with the type of Role Playing Games (RPG) games. The purpose of this study is to determine the Narrative Imitation, Entertainment, Simulation and Interaction (NESI) model in Role Playing Games on integer operation learning. The research method used is quantitative by using data sources from questionnaires and observations. The results of the study showed that the calculation of the results of the influence of the player's initial condition obtained a score of 76.4%, namely the pretest phase, there was an increase in scores of 11.2% to 87.6% in the middle test, namely learning using traditional methods and an increase of 18.8% to 95.2% at the end of the assessment. Furthermore, the analysis of game performance obtained a total average score of 90.78% of the aspects tested, so that the implementation of Role Playing Games (RPG) games has a positive influence on students in understanding mathematics lessons.